2021
DOI: 10.3390/ph14020173
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacokinetics and Biodistribution of Anticancer Dinuclear Palladium(II)-Spermine Complex (Pd2Spm) in Mice

Abstract: Palladium-based compounds are regarded as potential analogs to platinum anticancer drugs with improved properties. The present study assessed the pharmacokinetics and biodistribution of a dinuclear palladium(II)-spermine chelate (Pd2Spm), which has previously been shown to possess promising in vitro activity against several therapy-resistant cancers. Using inductively coupled plasma-mass spectrometry, the kinetic profiles of palladium/platinum in serum, serum ultrafiltrate and tissues (kidney, liver, brain, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…The pharmacokinetic profile and distribution of Pd 2 Spm is advantageous for cancer treatment. This compound induces a much faster metabolic response compared to cisplatin, so that the performance of the tested organs returns to its original state much earlier; thus, patients are expected to recover sooner than with cisplatin treatment [ 47 ].…”
Section: Modifications Of Platinum- and Palladium-based Moleculesmentioning
confidence: 99%
“…The pharmacokinetic profile and distribution of Pd 2 Spm is advantageous for cancer treatment. This compound induces a much faster metabolic response compared to cisplatin, so that the performance of the tested organs returns to its original state much earlier; thus, patients are expected to recover sooner than with cisplatin treatment [ 47 ].…”
Section: Modifications Of Platinum- and Palladium-based Moleculesmentioning
confidence: 99%
“…TNBC cells such as MDA-MB-231 cells demonstrated similar antiproliferative effects of Pd 2 Spm and cisplatin [ 11 ], but it was reported that breast cancer cells accumulate approximately four times lower amounts of Pd 2 Spm than cisplatin, i.e., a lower intracellular quantity of Pd 2 Spm is required to produce similar antiproliferative effects. This implies the occurrence of alternative (yet unknown) anticancer molecular target(s) for Pd 2 Spm versus cisplatin [ 15 , 16 , 17 , 18 ]. A recent pharmacokinetic study in mice also showed that while Pd 2 Spm has a very similar serum terminal half-life to cisplatin, it presents a lower accumulation in major organs as compared to cisplatin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This implies the occurrence of alternative (yet unknown) anticancer molecular target(s) for Pd 2 Spm versus cisplatin [ 15 , 16 , 17 , 18 ]. A recent pharmacokinetic study in mice also showed that while Pd 2 Spm has a very similar serum terminal half-life to cisplatin, it presents a lower accumulation in major organs as compared to cisplatin [ 15 ]. Therefore, Pd 2 Spm is expected to show a superior tolerability as well as lower nephrotoxicity/hepatotoxicity than cisplatin, owing to both lower tissue accumulation and decreased metabolic reactivity with kidney and liver biomolecules responsible for the associated toxicity (which was recently reported by our group) [ 15 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These are important limiting factors that adversely affect treatment outcomes and are mainly correlated with the accumulation of the chemotherapeutics in these organs [ 83 , 84 ]. Our recent comparative pharmacokinetic study in mice revealed a significantly lower accumulation of palladium (from Pd 2 Spm) in the lungs, brain, liver and heart, compared to platinum (from cDDP) [ 73 ]. Therefore, due to its lesser accumulation, Pd 2 Spm is not expected to cause significant deleterious effects (i.e., low cardiotoxicity and hepatotoxicity are expected) compared to cisplatin, thus establishing it as a promising alternative as a putative chemotherapeutic for breast cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the antimetastatic properties of Pd 2 Spm have been demonstrated through its anti-angiogenic and anti-migratory effects [ 72 ]. Moreover, Pd 2 Spm has exhibited favorable pharmacokinetics and biodistribution in healthy mice [ 73 ], thus increasing the interest in this compound as a promising pharmacological agent for cancer treatment. However, the potential cytotoxic effect of Pd 2 Spm needs to be further validated in in vivo cancer models, and this is the subject of ongoing work in our group.…”
Section: Introductionmentioning
confidence: 99%